HOTS-Speed Test untuk Meningkatkan Kemampuan Penalaran Analisis Peserta didik - Mahendra, I Wayan Eka; Jayantika, I G. A. N. Trisna; Sulistyani, Ni Wayan Rima (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2019)
The effect of HOTS-speed test based on problem-based learning (PBL) in improving analytical reasoning ability of students of class XI MIPA SMA N 1 Marga is the purpose of this study. By using factorial group design (treatment by subject); involving sample 132 students. HOTS-speed test and PBL are independent variables, as well as analytical reasoning abilities as the dependent variable. The data was collected using tests, namely: analytical reasoning ability tests, which have been tested for validity and reliability coefficients. The collected data were analyzed by two-way ANOVA, which previously tested the data distribution normality and variance homogeneity test. The results of the study indicate that there was an effect of HOTS-speed test setting of a problem-based learning model on the analytical reasoning ability of students. In order to obtain a more optimal analytical reasoning ability, the types of tests used must be considered.Â Key words: HOTS-Speed test, PBL, analytical reasoning ability